Art therapy interventions for active duty military service members with post-traumatic stress disorder and traumatic brain injury. Issue 2 (3rd April 2018) - Jones, Jacqueline P.; Walker, Melissa S.; Drass, Jessica Masino; Kaimal, Girija
ABSTRACT: This paper provides an overview of short and long-term art therapy treatment approaches, used in the USA, for military service members with post-traumatic stress disorder and traumatic brain injury. The described clinical approaches are based on the theoretical foundations and the art therapists' experiences in providing individualised care for the unique needs of the patient population. The art therapy models and directives are designed to be more therapist-led in the short-term model, moving on to an increasingly patient-led format in the long-term treatment model. The overall objectives of art therapy are: to support identity integration, externalisation, and authentic self-expression; to promote group cohesion; and to process grief, loss, and trauma. In addition, programme evaluation is used in both settings as a means to understand participants' experiences and the perceived value of art therapy.